Pengaruh Work Motivation, Work Discipline Dan Reward Terhadap Kinerja Driver Ojek Online Grab Di Kota Semarang - Cindy Iga Binarwati; Rauly Sijabat; Qristin Violinda (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of work motivation, work discipline and reward on the performance of Grab online motorcycle taxi drivers in the city of Semarang. This study used quantitative research methods. The population used in the study was Grab online motorcycle taxi drivers in Semarang year 2022 and the sample used was 100 respondents. Data analysis in the study using SPSS for window software version 26. The results of this study show that there is a positive and significant influence between work motivation (X1) on the performance of grab online ojek drivers in Semarang (Y) partially with a calculated t value of 6,833 and a significance value of 0.000, work discipline (X2) has a positive and significant effect on the performance of grab online motorcycle taxi drivers in Semarang (Y) partially with a calculated t value of 2,918 significance value of 0.4 reward (X3) has a positive and significant effect on driver performance Grab online motorcycle taxi in Semarang city (Y) partially with a calculated t value of 10,655 and a significance value of 0.000. The results of the coefficient of determination (R2) test obtained a value from Ajusted R Square of 0.915 or 91.5% showed that the performance variables of Grab online motorcycle taxi drivers in Semarang were influenced by work motivation, work discipline and reward variables, while the remaining 0.085 or 8.5% were influenced by other variables that were not in this study.